Coupling : strategies for infrastructural opportunism - Bhatia, Neeraj, (Pamphlet architecture, 2011)
Urbanism after form, Charles Waldheim -- Formatting contingency, infraNet lab/lateral office -- Fresh field, Keller Easterling -- Water ecologies/economies -- Land reservations -- Re-rigging -- The architectural reconstruction of geography, David Gissen -- Next north -- Wiring runways -- Icelink -- Afterword: figuring it out, Christopher Hight.